CERVICALGIA: A COMPARATIVE STUDY BETWEEN DIFFERENT PROCEDURESELECTROTHERAPEUTIC (Cuestiones de Fisioterapia, 2000)
Cervical pain is the most frequent among vertebral pains. So, we have carried out a comparative study between different electrical therapy technics. A population was taken randomly from those patients suffering from chronic cervical pain who were waiting for treatment at the Hospital Civil of Malaga. Two groups were established: the first one was treated with ultrasounds and microwaves; the second group was treated with ultrasounds and TENS. The outcomes seem to prove a better evolution in the group treated with ultrasounds and TENS, when talking about the evaluated parameters (pain and mobility)